2011
DOI: 10.1583/11-3475.1
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Hammer Syndrome

Abstract: We hypothesize that the etiology of the ulcer was the shear forces developed by incorrect, repetitive use of the pneumatic hammer in combination with the untreated hypertension. This is analogous to the hypothenar hammer syndrome, and we propose naming this the "aortic hammer syndrome."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Focusing on serious aortic complications, we only identified 3 cases of postoperative aortic rupture, 2 cases of fistula, and no aortic dissection. Surgical conversion during the postoperative course with thoracic stent-graft explantation was required in 1 patient because of a persistent type 1 endoleak [25]. Endoleaks are the second most frequent complication reported (8%), including type 1 in 9 cases, type 2 in 10, and type 3 or 4 in 6 cases.…”
Section: Commentmentioning
confidence: 99%
“…Focusing on serious aortic complications, we only identified 3 cases of postoperative aortic rupture, 2 cases of fistula, and no aortic dissection. Surgical conversion during the postoperative course with thoracic stent-graft explantation was required in 1 patient because of a persistent type 1 endoleak [25]. Endoleaks are the second most frequent complication reported (8%), including type 1 in 9 cases, type 2 in 10, and type 3 or 4 in 6 cases.…”
Section: Commentmentioning
confidence: 99%
“…Arterial lesions as a consequence of repeated blows are typical of the hypothenar hammer syndrome, in which the hand is used as a hammer, and the repeated blunt trauma may lead to arterial damage, thrombus formation, aneurysm of the ulnar artery or the superficial palmar arch, or microemboli formation, leading to digital ischemia. 6 Logically, therefore, Komen and colleagues 4 concluded that since atherosclerosis cannot be the pathogenic mechanism of PAU evolution in this particular patient, the shear forces of the repeated blunt trauma on the patient's chest by the pneumatic drill, in combination with the untreated hypertension, may very likely be the initiating mechanism of PAU development. Thus, they proposed calling this condition the “aortic hammer syndrome.”…”
mentioning
confidence: 93%
“…The case presented by Komen and colleagues 4 refers to a middle aged man with no evidence of atherosclerotic disease, an otherwise healthy aorta, and no CT findings of atherosclerotic lesions. Therefore, he cannot be considered as having a typical PAU.…”
mentioning
confidence: 99%
“…In their case, Komen et al 1 hypothesized that shear stress secondary to the hammer's repetitive blunt trauma was an etiologic factor in their case. However, they reported that the patient also suffered from severe hypertension.…”
mentioning
confidence: 96%
“…Recently, Komen et al 1 reported a patient with a penetrating aortic ulcer (PAU) in a “healthy” aorta. Since this acute aortic syndrome (AAS) arose in a demolition worker who had repeatedly used a pneumatic drill, they named it the “aortic hammer syndrome” (analogous with the “hypothenar hammer syndrome”).…”
mentioning
confidence: 99%